On the Application of Information Technology of Vietnamese Firms - Tu, Thuy Anh (H. : ĐHQGHN, 2018)
This paper aims at describing the current situation of the application of information technology (IT) in Vietnamese enterprises from 2001 to 2011. The analysis is taken in different dimensions: over time, by sector, and especially by firm ownership. We have evidence to state that in the research period, IT usage of Vietnam is rather limited. Especially for small firms, IT is still considered to be luxury. Only foreign firms or joint-stock companies pay enough attention to IT usage. From this analysis, policy discussions are withdrawn, mostly on how to speed up firms’ usage of IT to catch up with world business practices.